Narrative Policy Framework in The Academic Field: A Bibliometric Examination - Supardi, Stepanus; Alfitri, Alfitri; Widodo, Slamet; Thamrin, M.H. (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
The Narrative Policy Framework (NPF) has emerged as an indispensable instrument in public policy research, influencing the design, development, and implementation of diverse policies across multiple domains. Despite its growing application and influence, a thorough analysis and comprehension of its scholarly evolution and inter-disciplinary impact remain elusive. This study addressed this deficiency by conducting a comprehensive bibliometric analysis of the NPF literature. We extracted and analyzed 178 documents from the Scopus database using the Bibliometrix R utility. The results demonstrate a substantial increase in NPF research over the years, as evidenced by the growing number of affiliations and collaborations between researchers and institutions. In addition, the co-occurrence network analysis uncovered a number of research themes and clusters, providing valuable insights into the NPF research focus. Additionally, the study traced the thematic evolution of the research domain over time, revealing significant shifts and trends in research topics. Our findings suggest that the scholarly landscape of NPF research is diverse, complex, and dynamic, spanning multiple academic disciplines and policy domains. In addition to enhancing our comprehension of the NPF research ecosystem, the results of this study provide valuable insights for future research directions and policy applications.